Pengaruh Sistem Manajemen Mutu ISO 9001:2008 dan Partisipasi Penyusunan Anggaran Terhadap Kinerja Manajerial - U. Umiyati (ETIKONOMI, 2015)
The Effect of Quality Management System ISO 9001: 2008 and Budget Participation on Managerial PerformanceThe objective of this research is to analyze and to prove empirical evidence regarding with the influence of the application of quality management system of ISO 9001:2008 and the budget participation towards the improvement of managerial performance in State Islamic University (UIN) Syarif Hidayatullah Jakarta. The technique that used in this research is multiple linier regression. The result of this research proves the hypothesis build up before this research, that there significant influence between quality management system of ISO 9001:2008 and the budget participation towards the managerial performance, both through parameter test and simultaneous test. It shows that the application of quality system management ISO 9001:2008 and the budget participation done by State Islamic University (UIN) Syarif Hidayatullah Jakarta, influence the improvement of its managerial performanceDOI: 10.15408/etk.v14i1.2265